Adequately Adapted Insulin Secretion and Decreased Hepatic Insulin Extraction Cause Elevated Insulin Concentrations in Insulin Resistant Non-Diabetic Adrenal Incidentaloma Patients - Anderwald, Christian-Heinz; Tura, Andrea; Gessl, Alois; Luger, Anton; Pacini, Giovanni; Krebs, Michael (PLOS ONE, 2013)
BackgroundInsulin-resistance is commonly found in adrenal incidentaloma (AI) patients. However, little is known about beta-cell secretion in AI, because comparisons are difficult, since beta–cell-function varies with altered insulin-sensitivity. ObjectivesTo retrospectively analyze beta–cell function in non-diabetic AI, compared to healthy controls (CON). MethodsAI (n=217, 34%males, 57±1years, body-mass-index:27.7±0.3kg/m2) and CON [n=25, 32%males, 56±1years, 26.7±0.8kg/m2] with comparable anthropometry (p≥0.31) underwent oral-glucose-tolerance-tests (OGTTs) with glucose, insulin, and C–peptide measurements. 1mg-dexamethasone-suppression-tests were performed in AI. AI were divided according to post–dexamethasone-suppression–test cortisol-thresholds of 1.8 and 5µg/dL into 3subgroups: pDexa<1.8µg/dL, pDexa1.8-5µg/dL and pDexa>5µg/dL. Using mathematical modeling, whole-body insulin-sensitivity [Clamp-like-Index (CLIX)], insulinogenic Index, Disposition Index, Adaptation Index, and hepatic insulin extraction were calculated. ResultsCLIX was lower in AI combined (4.9±0.2mg·kg-1·min-1), pDexa<1.8µg/dL (4.9±0.3) and pDexa1.8-5µg/dL (4.7±0.3, p<0.04 vs.CON:6.7±0.4). Insulinogenic and Disposition Indexes were 35%–97% higher in AI and each subgroup (p<0.008 vs.CON), whereas C–peptide–derived Adaptation Index, compensating for insulin-resistance, was comparable between AI, subgroups, and CON. Mathematical estimation of insulin–derived (insulinogenic and Disposition) Indexes from associations to insulin-sensitivity in CON revealed that AI-subgroups had ~19%-32% higher insulin-secretion than expectable. These insulin-secretion-index differences negatively (r=-0.45, p<0.001) correlated with hepatic insulin extraction, which was 13-16% lower in AI and subgroups (p<0.003 vs.CON). ConclusionsAI-patients show insulin-resistance, but adequately adapted insulin secretion with higher insulin concentrations during an OGTT, because of decreased hepatic insulin extraction; this finding affects all AI-patients, regardless of dexamethasone-suppression-test outcome.